2010
DOI: 10.1042/bj20100293
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish: gaining popularity in lipid research

Abstract: Zebrafish are an increasingly popular vertebrate model organism in which to study biological phenomena. It has been widely used, especially in developmental biology and neurobiology, and many aspects of its development and physiology are similar to those of mammals. The popularity of zebrafish relies on its relatively low cost, rapid development and ease of genetic manipulation. Moreover, the optical transparency of the developing fish together with novel imaging techniques enable the direct visualization of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 61 publications
1
120
0
1
Order By: Relevance
“…The YSL has an important function in transporting nutrients from the yolk to the embryonic cells and later to larval tissues and is also responsible for the degradation of some nutrients (Carvalho and Heisenberg, 2010;Hölttä-Vuori et al, 2010). It has been demonstrated before that injection into the yolk during the epiboly stage leads to successful diffusion of the injected material within the yolk without later outward flux (Hagedorn et al, 1997;Janik et al, 2000;Robles et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…The YSL has an important function in transporting nutrients from the yolk to the embryonic cells and later to larval tissues and is also responsible for the degradation of some nutrients (Carvalho and Heisenberg, 2010;Hölttä-Vuori et al, 2010). It has been demonstrated before that injection into the yolk during the epiboly stage leads to successful diffusion of the injected material within the yolk without later outward flux (Hagedorn et al, 1997;Janik et al, 2000;Robles et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…Additionally, tank densities were different between the two studies, with the current study having three times the density of the previous work (e.g., current: *5.5 fish/L vs. *1.6 fish/L). 24 Although the zebrafish model has garnered much recent attention for its potential use in lipid and obesity research, [41][42][43][44][45][46][47] few studies have reported overall body composition outcomes. In the present work, the dietary protein source significantly impacted lean and fat mass outcomes.…”
Section: Smith Et Almentioning
confidence: 99%
“…In addition, abnormal intravascular lipid metabolism is a major promoter of atherosclerosis, which may deteriorate into coronary disease and cerebral arterial thrombosis. Zebrafish (Danio rerio), with transparent embryos, external fertilization, clutch size and moderate generation time has functioned as an important vertebrate model (4,5). There have been numerous lipid studies focused on the alimentary system, saccus vitellinus, angiogenesis and the nervous system (6,7).…”
Section: Introductionmentioning
confidence: 99%